Evaluation of droplet deposition and effect of variable-rate application by a manned helicopter with AG-NAV Guía system - Yao, Weixiang; Lan, Yubin; Wen, Sheng; Zhang, Huihui; Zhang, Yali; Wang, Juan; Xie, Chunchun (International Journal of Agricultural and Biological Engineering, 2019)
The variable-rate application is an important aspect of precision agriculture. In order to determine the regular patterns of droplet deposition and compare the actual variable-rate spraying effect of the AS350B3e helicopter with the AG-NAV Guía system, spray tests were conducted with different operating parameters and operating methods. In this study, the deposition distribution of droplets in the effective swath area was evaluated for six single-pass applications at four different flight velocities. The effects of adding adjuvant on droplet deposition, drift and droplet size were compared, and the actual variable effect of the forth-back application was verified. The analysis results showed that the position of the effective swath area was affected by natural wind velocity and wind direction, and would shift to the downwind direction area from the helicopter route of a different degree. The effective swath width increased slowly and then decreased sharply with the increase of flight velocity. It was found that flight velocity of 100 km/h was the peak inflection point of effective spray width variation. Moreover, the effect of flight velocity on the distribution uniformity of droplet deposition in the effective swath area was not significant. In the single-pass application of 90 km/h, adding adjuvant could increase droplet size in the effective swath area. The deposition increased by 8.98%, and the total drift decreased by 28.65%, of which the upwind drift decreased by 28.31% and the downwind drift decreased by 29.06%. In the forth-back application of 90 km/h, the error between actual application volume and system setting dose was 12%. The results of this study can provide valuable references for future research and practices on variable-rate aerial applications by manned helicopters. Keywords: manned helicopter, precision agriculture, variable-rate aerial application, spray test, adjuvant, droplet deposition DOI: 10.25165/j.ijabe.20191201.4039 Citation: Yao W X, Lan Y B, Wen S, Zhang H H, Zhang Y L, Wang J, et al. Evaluation of droplet deposition and effect of variable-rate application by a manned helicopter with AG-NAV Guía system. Int J Agric & Biol Eng, 2019; 12(1): 172–178.